Flexible Crisis Management Through Teleworking - Malatyinszki, Szilárd; Petrohai, Orsolya; Végh, Klaudia (Journal of Cultural Analysis and Social Change, 2025)
This study examines flexible crisis management through teleworking and home office practices in a large multinational company during and after the COVID-19 pandemic. Using a mixed-methods approach, the research combines a literature review with empirical data from a questionnaire survey (N=104) and in-depth interviews with a manager, an HR professional, and an employee. The findings show that the pandemic accelerated the adoption of teleworking and contributed to organisational innovation. Remote work generally improved employee efficiency, supported work–life balance, and strengthened employee engagement, despite initial challenges related to managerial control, trust, and IT infrastructure. These challenges were largely addressed through performance-based monitoring, digital tools, and hybrid working models. The study concludes that teleworking, when supported by trust-based leadership and a flexible organisational culture, represents a sustainable and effective long-term strategy for crisis management and organisational resilience. From a sustainability perspective, efficiency-oriented organisational practices contribute to long-term resilience and resource optimisation, supporting the strategic relevance of teleworking beyond crisis periods (Kálmán, 2024).